PENCIPTAAN BUKU ILUSTRASI TENTANG PENTINGNYA SAYURAN SEBAGAI MEDIA EDUKASI BAGI ANAK-ANAK - Pradityo, Dito Febry; Bahruddin, Muh; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2016)
Abstract: Seeing the growth in the modern era of such as this the increasing number of fast food that circulate in the canteens of school children and diminished fibrous foods such as vegetables. The problem, nutritious foodsparticularly vegetables now rarely known by the person if the nutrients contained in vegetables high protein. Vegetables are the main source of minerals for the children there are a few types of vegetables containing iron, potassium and phospor. This is because there is a lot of media who publish, particularly through the book in the form of vector which is accompanied puzzle game. Though vegetables are foods that are high in fiber needed by the body to keep the body becomes healthy and fit. In addition, if not eating vegetables will also interfere with the growth and cause vision problems such as blindness and xerophthalmia or dryness of the membranes and corneal mata.tetapi still many people who tend to avoid the vegetables for the body. In this study indicate that children do not despise to vegetables because of bitter taste. For the purpose of this study was to create an illustrated book on the importance of vegetables as a medium of education for children.Keywords: Vegetables, Children, Book Illustration, Vector, Design